Marketing Today - Oliver Gordon (Prentice Hall, 1980)
The first British comprehensive introductory text that combines an analytical approach to marketing problems with practical guidance in the application of marketing techniques. Preface, The Role of Marketing, Consumer Psychology, Social Influences on Buyer Behavior, Models of Buyer Behavior, Organizational Buyer Behavior, Market Segmentation, Marketing Research, Sales Forecasting and Market Potential, Developing Marketing Strategy, Product Planning, Test Marketing and Brand Launch Analysis, Promotional Planning, Advertising Objectives and Assessment, Advertising Media Planning, Sales Force Planning, Channel Structure and Conduct, Price Planning, Organizing and Appraising Marketing Operations, Challenges to Marketing, Glossary, Index.